EFIKASI DIRI AKADEMIK DAN OPTIMISME DENGAN RESILIENSI AKADEMIK SISWA YANG BELAJAR DARING DI SMAN 2 CIKARANG UTARA - Real Monata; Agustina Ekasari; Devi Puspitasari (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2022)
This study aims to determine the relationship between Academic Self-Efficacy and optimism with the academic resilience of the students studying online at SMAN 2 Cikarang Utara. This research will use quantitative method with research design using correlation and regression. The subject in this study were high school student who were studying online, which consisted of three classes, grades 10, 11, 12 totaling 138 student. This study uses a standard scale. The results of Alpha Cronbach formula include, The Academic Resilience Scale-30 with a value r=0,907, Online Learning Self-Efficacy Scale (OLSES) with a value r=0,755, and Life Orientation Test Revised (LOT-R) with a value r= 0,441. Data anaylsis technique used rank spearman correlation and multiple regression test. The results of the correlation test between academic self-efficacy and academic resilience showed a positive and significant relationship with the value of sig= 0, 000 (< 0,05), while the correlation test between optimism and academic resilience showed a positive and significand relationship with the value of sig= 0, 000 (<0,05). On the results of multiple regression tests between academic self-efficacy and optimism on academi on academic resilience show a significant effect with a value of sig= 0, 000 (<0,05)